Structure-property characterization of the dentine-enamel junction (DEJ) - Sui, T; Li, T; Sandholzer, M; Bourhis, E; Zeng, K; Landini, G; Korsunsky, A (Newswood Limited, 2014)
The dentine-enamel junction (DEJ) is an Important internal interface with strong and durable bonding between the hard outer layer (enamel) and the soft inner tooth core (dentine). This study investigated the microstructure of the DEJ by X-ray imaging method and synchrotron X-ray scattering techniques. Further high resolution elastic modulus mapping indicates that the DEJ is a band with a graded mechanical property rather than a discrete interface. The microstructure-property relationship is also illustrated. The knowledge of the architecture and properties of the natural DEJ will help in the biomimetic development of dental restorations and novel replacement materials and application techniques.